Microstructural evolution and mechanical behavior of resistance spot welded FeCrNiSiB advanced high-strength steel - Mohammad Hossein Amini-Chelak; Hossein Aliyari; Reza Miresmaeili; Azin Katourani; Hamid Reza Shahverdi; Mohsen Askari-Paykani (Journal of Materials Research and Technology)
This study examines the microstructural evolution and mechanical performance of resistance spot welded joints in a newly developed FeCrNiSiB advanced high-strength steel (AHSS). The effects of key welding parameters—current (4–7 kA), weld time (9–21 cycles), and electrode force (2–4 kN)—on nugget formation and failure behavior were systematically investigated through 24 welding trials. Lobe curves were constructed at three force levels to define optimal processing windows, showing narrower weldability ranges at higher forces. Microstructural analysis revealed a dendritic austenitic matrix interspersed with eutectic boride phases (M2B) in the fusion zone (FZ), while the partially melted zone (PMZ) exhibited partially liquefied grains with similar eutectics. Hardness in the FZ reached 1.5 times that of the base metal due to boride enrichment. Tensile-shear tests indicated a failure mode transition—from interfacial (IF) to partial interfacial (PIF), and eventually to partial thickness–partial pullout (PT-PP)—as nugget size increased. For welds with nugget diameters above 4 mm, joints exceeded the minimum tensile-shear strength requirement by approximately 14 %. These findings demonstrate the influence of welding parameters on microstructure, hardness, and localized mechanical response in this novel boron-alloyed AHSS.